NEW MONOGRAPH ON MEDIEVAL AZERBAIJAN WEAPONS. SABUKHI AKHMEDOV’S “AZERBAIJAN WEAPONS IN THE IX―XVII CENTURIES: EVOLUTION AND DEVELOPMENT” - Gusejn, Farah Adil' kyzy (History, Archeology and Ethnography of the Caucasus, 2019)
The article is a review on Ph.D. Sabukhi Akhmedov’s monograph «Azerbaijani weapons in the IX – XVII centuries: evolution and development», which considers the relevance and scientific validity of the issue as an «Azerbaijani weapons», noted that the problem of identification of various types of weapons made in Azerbaijan during the Middle Ages is relevant in geographical attribution, as well as belonging to a certain ethnocultural space established in a given territory.The article provides a general assessment of the wide range of diverse sources involved in the study, justifies the logical consistency of the structure of the monograph built on the principle of chronological order, recognizes the importance of the monograph in studying the history of military affairs in Azerbaijan and neighboring countries in the Middle Ages.
Keywords: Azerbaijani weapons; cold weapons; firearms; medieval period; artefacts; museum exhibits; tulbend (helmet).